2013
DOI: 10.4103/0970-1591.117283
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shock wave lithotripsy today

Abstract: Even 32 years after its first introduction shockwave lithotripsy (SWL) remains a matter of discussion and controversy. Since the first SWL in 1980, millions of treatments have been performed worldwide. To this day SWL remains the least invasive of all stone treatments and is considered the treatment modality of first choice for the majority of urinary stones. Despite the massive scale on which SWL is performed in a wide range of indications, complication rate has always remained very low and usually limited to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 35 publications
(16 reference statements)
0
12
0
1
Order By: Relevance
“…The next steps in the SWL procedure are identification of the target and optimal positioning of the patient [ 1 , 3 , 92 ]. Fluoroscopy is most commonly used [ 14 ], but ultrasound might also be used. The latter technique is used for identification of the radiolucent uric acid stones as an alternative to contrast medium.…”
Section: Technical Aspects On How To Carry Out the Shockwave Procedurmentioning
confidence: 99%
“…The next steps in the SWL procedure are identification of the target and optimal positioning of the patient [ 1 , 3 , 92 ]. Fluoroscopy is most commonly used [ 14 ], but ultrasound might also be used. The latter technique is used for identification of the radiolucent uric acid stones as an alternative to contrast medium.…”
Section: Technical Aspects On How To Carry Out the Shockwave Procedurmentioning
confidence: 99%
“…Symptomatic or clinically significant bleeding requiring blood replacement occurs in approximately 2 out of 1,000 treated patients. Similarly, a large multicentre study assessed the incidence of renal haematomas at 0.5 and 0.14 % following ESWL treatment of renal and ureteral stones respectively [ 4 , 9 11 , 13 16 ]. Retroperitoneal haemorrhage after ESWL may cause haemodynamic shock and occasionally be fatal [ 17 , 18 ].…”
Section: Minimally Invasive Treatment Of Urolithiasismentioning
confidence: 99%
“…Many medical centres are concerned about the adverse effects of ESWL on tissues [14] . Clinical and experimental studies have shown that this treatment might have severe, acute and chronic effects on the kidney and its peripheral tissues [15] , [16] , [17] .…”
Section: Discussionmentioning
confidence: 99%